Ecology of orchids in urban bushland reserves – can orchids be used as indicators of vegetation condition? - Newman, Belinda; Ladd, Phil; Batty, Andrew; Dixon, Kingsley (Lankesteriana: International Journal on Orchidology, 2015)
The loss of urban native vegetation is a global cri- sis particularly as cities continue to expand and pop- ulations grow. Native vegetation often remains as small isolated fragments embedded in the human matrix of urban development. These remnants become islands of biodiversity that experience vary- ing degrees of degradation due to their high perime- ter to area ratio.